PENGARUH KOMITMEN PROFESIONAL, LINGKUNGAN ETIKA, SIFAT MACHIAVELLIAN DAN PERSONAL COST TERHADAP INTENSI WHISTLEBLOWING DENGAN RETALIASI SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Perbankan yang berada di Kota Pekanbaru) - Taufiq Nugraha; Nur Azlina; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examines the effect of proffesional commitment, environmental ethics, machiavellian and personal cost on Intention whistleblowing, and Retaliation as Moderating Variable. The sample of this study is auditors of 39 banking companies that listed in the Pekanbaru city. Analytical techniques used to perform the hypothesis testing is purposive sampling. Data are analyzed using multiple regression method using SPSS 20 version. The results showed that Professional commitment has effect by significance value as 0.035 and H1 accepted. Variable Environtmental ethical has effect by significance value as 0.000 and H2 is accepted. Machiavellian variables has effect by significance value as 0.026 and H3 accepted. Variable Personal Cost has effect by significance value as 0.008 and H4 accepted. Variable Proffessional Cimttment has effect and moderated by Retaliation with significance value as 0,000 and H5 accepted. Variable Environtmental Ethic has effect and moderated by Retaliation with significance value as 0,000 and H6 accepted. Variable Machavellian has effect and moderated by Retaliation with significance value as 0,012 and H7 accepted. Variable Personal Cost has effect and moderated by Retaliation with significance value as 0,006 and H5 accepted.Keyword: Whistleblowing, Commitment, Environtmental, Machiavellian, Cost, Retaliation.